Language Learning Anxiety in Online Learning: Malaysian ESL Undergraduates' Perspectives - Mahmud, Nazirah; Mazeree, Nur Syasya Qistina; Mahmud, Najihah (Institut Agama Islam Negeri Ponorogo, 2023)
The pandemic has changed the dynamics of the educational system, which has drastically turned toward remote learning. This sudden shift from conventional classroom instruction to online learning has affected the students' performance as second language learners. This study focuses on how undergraduate students perceive language learning anxiety when widespread online learning is implemented. This study used a quantitative approach through an adapted questionnaire to gather perspectives from 168 undergraduate students enrolled in online English language courses at a public institution in Malaysia. An analysis of the items was carried out using SPSS software. The findings showed that communication apprehension and fear of negative evaluation are the most prominent factors contributing to students’ language learning anxiety. Test anxiety, on the other hand, was reported to be the least important element. This study suggested that the implementation of online learning may influence the students’ language learning anxiety, and this was further examined along with recommendations for future research.